Comparison of fracture resistance between nanohybrid and bulk-fill resin using incremental and mono-incremental Techniques. - Albán Hurtado, Carlos Alberto; Sánchez Varela, Galo; Vélez Cuenca, Tatiana Maricela; Merino Segovia, Andrea Carolina (SATHIRI, 2019)
This research aimed to compare the fracture resistance between nanohybrid and Bulk-Fill resin using incremental and mono-incremental techniques. This is a comparative study in-vitro, non- random sample. Probes 5 mm high by 6 mm in diameter are used in four groups; group A with 10 specimens of conventional resin (nanohybrid) with application in the incremental technique, group B with 10 specimens of conventional resin (nanohybrid) with the application in the mono-basic technique, group C with 10 specimens of resin Bulk Fill with the application in the incremental technique, and group D with 10 Bulk Fill resin specimens with application in mono-basic technique; Each time a compression was tested with a universal test compression machine until its fracture. Data were analyzed to determine if a normal distribution with the Shapiro-Wilk test. The t-Student parametric test was applied for the statistical analysis; Which proved its reliability with the Levene test. The results showed that the fracture resistance of conventional resin with incremental technique on average was 219,998 MPa, and with mono-basic technique 122,771 MPa; The fracture resistance of Bulk Fill resin with incremental technique on average was 246.433 MPa, and with mono-basic technique 251.322 MPa. It is concluded that there is a significant difference between the fracture resistance of conventional resin (nanohybrid) and Bulk Fill resin with incremental and mono- incremental techniques.